2018
DOI: 10.2144/btn-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Absolute bioluminescence imaging at the single-cell level with a light signal at the Attowatt level

Abstract: Bioluminescence imaging (BLI) demonstrates cellular events as a light signal at the single-cell level using a highly sensitive, cooled CCD camera. However, BLI signals are relative values and thus, images taken on different days or using different equipment cannot be compared directly. We established a reference LED light source that was characteristic of the total flux and light distribution and calibrated the BLI system as an absolute light signal. This calibrated BLI system revealed that the average light s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Although we have not compared the LuminoCell with other commercial devices, it is of note, however, that this luminometer cannot compete with commercial instruments in terms of detection limits. While this simple luminometer has a detection limit around 40 pW/s of light irradiance (TSL237S-LF has irradiance responsivity of 2.3 kHz/(μW/cm 2 )), devices equipped with expensive PMT tubes, or special CCD cameras offer much better sensitivity in attowatts (Enomoto et al, 2018). The relatively low detection limit of light irradiance is, however, estimated for 1 second of integration time.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not compared the LuminoCell with other commercial devices, it is of note, however, that this luminometer cannot compete with commercial instruments in terms of detection limits. While this simple luminometer has a detection limit around 40 pW/s of light irradiance (TSL237S-LF has irradiance responsivity of 2.3 kHz/(μW/cm 2 )), devices equipped with expensive PMT tubes, or special CCD cameras offer much better sensitivity in attowatts (Enomoto et al, 2018). The relatively low detection limit of light irradiance is, however, estimated for 1 second of integration time.…”
Section: Discussionmentioning
confidence: 99%
“…Total average CEA in one section was approximately 460 ng/tissue (Supplementary Figure 1). Previous research using radioimmunoassay has suggested that tumor tissues contain Benchmark around 145-17,850 ng/mg CEA [7]. A bicinchoninic acid assay of another frozen section found about 0.03 mg total protein, indicating around 15,000 ng/mg CEA.…”
Section: Introductionmentioning
confidence: 93%
“…Using this LED, time-averaged emission intensity could be controlled linearly to cover a wide dynamic range of about four orders of magnitude for several years. This calibrated BLI system revealed that luciferase had an average light signal at one attowatt, corresponding to a few thousand photons per second per cell [7]. Based on luciferase quantum yield, we could estimate the amount of luciferase protein in a living cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the bioluminescence intensity emitted by a single mammalian cell-expressing beetle luciferase was estimated to be between 1100–2500 photons s −1 , and the number of luciferase molecules expressed inside the cell was estimated to be approximately 2000–3000 molecules [ 97 ]. However, one limiting factor for attaining high intensity could be oxygen availability, especially in deep tissues under anoxic conditions.…”
Section: Is It Possible To Report In Two Dimensions?mentioning
confidence: 99%